Experimental investigation of the effects of plastic flow in a tension panel with a circular hole - Griffith, George E. (National Advisory Committee for Aeronautics, 1948)
Seven uniformly dimensioned 24S-T tension panels with a central circular hole were subjected to various loads in order to study the effects of plastic flow at the point of maximum stress concentration. The results, presented in graphical form, show that, as the amount of plastic flow increases, the stress concentration factor is appreciably reduced and the strain concentration factor is appreciably increased. Subjecting the panels to 100 repeated loading cycles caused no change to occur in the maximum values of the stress and strain concentration factors.
"September 1948."
NACA TN No. 1705.
Keywords: Aluminum alloys.; Plates (Engineering); Holes.; Loads (Mechanics); Alloys -- Creep.; Strains and stresses.; elektronické knihy; electronic books